Transforming higher education: motivating academics for social innovation - Hai-Ninh Do; Thi Kim Thanh Do (Cogent Education)
In this fast and unprecedented changing world, graduate students are to be competent in dealing with the social problems and contribute to uplift the communities and save the planet they are living in. It is undeniable that academics play a crucial role in helping students to achieve the mentioned outcomes. The purpose of this study is to explore the factors influencing the pursuit of institutional work for social innovation among academics in Vietnamese higher education institutions (HEIs). A qualitative research design along with the theories of self-determination and institutional work was deployed. Twelve participants, who are practitioners, researchers and lecturers from a social enterprise and seven universities across Vietnam, were invited to join seven deep interviews conducted in the form of individual conversations and focus groups. A hybrid methodology of both inductive and deductive reasoning provides significant opportunities to approach and obtain the robust analysis of the empirical data. Apart from the findings of specific needs that successfully motivate the academics, the study also highlights the factors influencing SI promotion among academics in Vietnamese HEIs. Feasible initiatives are also recommended for practitioners seeking to cultivate social innovation within HEIs. The study also offers avenues for further research and exploration in the domain of psychological needs and institutional work.